Enzymatic Extract from Luffa-Immobilized Pleurotus sajor-caju: A Promising Biocatalyst for Agro-Industrial Pollutant Reduction and Toxicity Mitigation - Fernandes, Clara Dourado; de Castro, Vera Lucia Scherholz Salgado; Vallim, José Henrique; Wani, Atif Khurshid; Américo-Pinheiro, Juliana Heloisa Pinê; Serejo, Teresa; Pereira, Rinaldo Wellerson; Egues, Silvia Maria; Romanholo Ferreira, Luiz Fernando (Topics in Catalysis, 2024)
In biotechnological methods for biodegradation, the effectiveness of detoxifying xenobiotics and recalcitrant substances in soil and water has sparked significant interest. Our study takes a unique approach by focusing on immobilizing the white-rot fungus (WRF) Pleurotus sajor-caju onto a Luffa cylindrica plant support. This innovative method aims to facilitate the mycoremediation of agro-industrial pollutant pulp wash generated by the orange industry. The immobilization process significantly increased MnP enzymatic activity, reaching 23 IU.mL−1 and Lac activity at approximately 40.5 IU.mL−1. Qualitative SEM and FTIR analyses provided insights into the microorganism’s attachment mechanism to the support, suggesting that aggregation occurs due to an affinity to the lignocellulosic structure, enhancing the production of polysaccharides responsible for biocatalyst adherence and potential reusability. Furthermore, the production of an enzymatic extract rich in ligninolytic enzymes from P. sajor-caju showcased its ability to reduce the toxicity of pulp wash. An exploration into the toxicity of citrus effluent revealed the generation of embryos with severe deformities and the inhibition of Lactuca sativa germination, even at low concentrations. Notably, post-treatment with the enzymatic extract resulted in a remarkable 90% reduction in toxicity to the trophic level of Danio rerio and lettuce seeds. This research significantly contributes to understanding fungal immobilization strategies in environmental biotechnology, emphasizing the potential of agricultural residues as sustainable inducers for enzyme production and their pivotal role in mitigating the environmental impact of agro-industrial waste.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Cytotoxicity; Laccase; Manganese peroxidase; Wastewater from agro-industrial